ACCOUNTING TREATMENT OF PRODUCING PLANTS AND NOT YEARING PALM OIL CULTIVATION AT PT PERKEBUNAN NUSANTARA III (HOLDING) - Sinaga, Nurkhotimah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This research aims to know describing briefly about accounting treatment of mature plants and immature plants of palm oil cultivation at PT Perkebunan Nusantara III (holding). This research is in case/field research, with the characteristics of the problem referring to the background and condition nowdays of the subjects studied, it is immature plants and mature plants, so that a complete picture is obtained regarding this matter. In this research, using descriptive method and comparative method in analyzing the data. In descriptive method, the researcher collected, compiled, classified the data obtained and then interpreted and analyzed it so as to provide complete information and description regarding the accounting treatment of immature plants and mature plants of palm oil cultivation at PT Perkebunan Nusantara III (holding). Eventhough in comparative method is used to compare the accounting treatment of mature plants and immature plants of palm oil cultivation in the company's financial statements with the accounting treatment in the financial statements that refers to PSAK No. 16 (2015), OJK Regulation (2021), and Pedoman Akuntansi BUMN Perkebunan (PABP) 2008, which are generally accepted in Indonesia. The data collected is secondary data. Using documentation techniques in data collection. The results of this study indicate that the accounting treatment for immature plants and mature plant of Palm Oil Cultivation at PT Perkebunan Nusantara III (holding). is generally in accordance with PSAK No. 16 (2015), OJK Regulation (2021), and Pedoman Akuntansi BUMN Perkebunan (PABP) 2008.